Epitope prediction and confirmation for the human androgen receptor: Generation of monoclonal antibodies for multi-assay performance following the synthetic peptide strategy - Zegers, Netty D.; Claassen, Eric; Neelen, Conny; Mulder, Eppo; van Laar, Jacoba H.; Voorhorst, Margreet M.; Berrevoets, Cor A.; Brinkmann, Albert O.; van der Kwast, Theodorus H.; Ruizeveld de Winter, Jacobus A.; Trapman, Jan; Boersma, Wim J.A. (Biochimica et biophysica acta, 1991)
The human androgen receptor (hAR) is an important regulatory protein particularly in male sexual differentiation. The investigation of hAR functionality has been hampered by the lack of AR specific monoclonal antibodies recognizing the functional domains of the receptor. Therefore production of high affinity mono-specific polyclonal (PAbs) and monoclonal antibodies (MAbs) directed to the hAR was initiated following the synthetic peptide (SP) strategy. Five hAR specific peptides were selected on the basis of their predicted antigenic properties avoiding homology with other steroid hormone receptors. Peptide specific polyclonal antisera were obtained following selected immunization protocols. Mono-specific polyclonal antibody responses were elicited to all peptides in mice and rabbits. Crossreactivity of the peptide specific antisera with the native hAR in various biochemical assays was observed with two out of five peptides. Peptide SP61 (hAR residues 301–320) was used for the generation of site-directed MAbs specific for the hAR. Specificity for the hAR was established by immunoprecipitation, immune-complex density gradient centrifugation and immunohistochemistry on human prostate tissue sections. The multi-assay performance of the selected high affinity antibodies proved the usefulness of the straight forward peptide approach and opens a wide field of possible biochemical and physiological investigations into questions related to androgen action.